Ben Sira in conversation with traditions - Macatangay, Francis M.,Ruiz-Ortiz, Francisco-Javier,Egger-Wenzel, Renate,Calduch-Benages, Nuria (Walter de Gruyter GmbH, 2022)
The series Deuterocanonical and Cognate Literature Studies (DCLS)is concerned principally with research into those books of the Greek Bible (Septuagint) which are not contained in the Hebrew canon, and into intertestamentary and early Jewish literature from the period around the 3rd century BCE to the 2nd century CE. The series was launched in 2007 in collaboration with the
Description based on publisher supplied metadata and other sources
Keywords: Festschrift; Electronic books